2017
DOI: 10.1016/j.neuro.2017.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Sex- and brain region- specific effects of prenatal stress and lead exposure on permissive and repressive post-translational histone modifications from embryonic development through adulthood

Abstract: Developmental exposure to prenatal stress (PS) and lead (Pb) can affect brain development and adversely influence behavior and cognition. Epigenetic-based gene regulation is crucial for normal brain development and mis-regulation, in any form, can result in neurodevelopmental disorders. Post-translational histone modifications (PTHMs) are an integral and dynamic component of the epigenetic machinery involved in gene regulation. Exposures to Pb and/or PS may alter PTHM profiles, promoting lifelong alterations i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 60 publications
2
25
0
Order By: Relevance
“…One study has shown, for example, that prenatal exposure to lead was associated with hypermethylation of three regions in hippocampal tissue for female, but not male, adult mice (Sánchez-Martín et al, 2015). Another study has shown that prenatal exposure to lead was associated with histone modifications, some of which had sex-and tissue-dependent effects (Schneider, Anderson, Kidd, Sobolewski, & Cory-Slechta, 2016;Varma, Sobolewski, Cory-Slechta, & Schneider, 2017).…”
Section: Lead-induced Epigenetic Changementioning
confidence: 99%
“…One study has shown, for example, that prenatal exposure to lead was associated with hypermethylation of three regions in hippocampal tissue for female, but not male, adult mice (Sánchez-Martín et al, 2015). Another study has shown that prenatal exposure to lead was associated with histone modifications, some of which had sex-and tissue-dependent effects (Schneider, Anderson, Kidd, Sobolewski, & Cory-Slechta, 2016;Varma, Sobolewski, Cory-Slechta, & Schneider, 2017).…”
Section: Lead-induced Epigenetic Changementioning
confidence: 99%
“…Subsequent extension of these studies to a panel of 4 PTHMs (global levels of H3K9ac, H3K4Me3, H3K9Me2 and H3K27Me3) examined at embryonic day 18 and PND0, 6 and 60 in FC and HIPP further underscored these complexities [39]. Sex, brain region and time-dependent changes occurred in controls even in the absence of Pb±PS.…”
Section: Introductionmentioning
confidence: 99%
“…Results from these studies indicate that at any given time point, global PTHM profiles differ by context, i.e., developmental exposure conditions (control, Pb, PS or Pb+PS), sex and brain region , as summarized in Table 1 adapted from data taken at PND6 from a recently reported study from our laboratories [39]. It presents changes in the expression levels of the 4 PTHMs (H3K9Ac, H3K4Me3, HeK9Me2 and H3K27Me3) as a percent of control group expression levels (100%) for all treatment groups (rows) [39], with arrows indicating direction of change.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations